2013
DOI: 10.1111/gcb.12339
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the response of an Arctic top predator experiencing habitat loss: feeding and reproductive ecology of two polar bear populations

Abstract: Polar bears (Ursus maritimus) have experienced substantial changes in the seasonal availability of sea ice habitat in parts of their range, including the Beaufort, Chukchi, and Bering Seas. In this study, we compared the body size, condition, and recruitment of polar bears captured in the Chukchi and Bering Seas (CS) between two periods (1986-1994 and 2008-2011) when declines in sea ice habitat occurred. In addition, we compared metrics for the CS population 2008-2011 with those of the adjacent southern Beaufo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
203
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 190 publications
(233 citation statements)
references
References 68 publications
(129 reference statements)
20
203
3
Order By: Relevance
“…Bears across the region appear to be in relatively good physical condition. These reports coincide with a recent study that observed no change in body condition and reproductive indices between polar bears captured in this region in 1986 -94 and those captured in 2008 -11 (Rode et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Bears across the region appear to be in relatively good physical condition. These reports coincide with a recent study that observed no change in body condition and reproductive indices between polar bears captured in this region in 1986 -94 and those captured in 2008 -11 (Rode et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…These reports converge with Western scientific observations that body masses and skull widths of adult males in the Chukchi Sea are among the highest of any reported for polar bears in the spring (Manning, 1971;Rode et al, 2014), including perhaps the largest male ever weighed in the spring, at 632 kg (USFWS, unpubl. data).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Polar bears use ice for migration, mating, and to prey on seals. With reductions in sea ice, the sea-ice habitat will shrink substantially and the numbers of both polar bears and ice-dependent seals are expected to decline (Loeng et al, 2005;Durner et al, 2009;Rode et al, 2014;Laidre et al, 2015). Polar bears may have to retreat to land, which will likely lead to increased starvation for lack of appropriate food and declines in abundance (Hamilton et al, 2014).…”
Section: Effects Of Advective Changes On Seabirds and Marine Mammalsmentioning
confidence: 99%
“…Fragmentation and decreased spatial and temporal availability of their sea ice habitat can have negative impacts on the accessibility of their primary prey, i.e., seals (Derocher, 2010;Durner et al, 2009;Wiig, 2005). For example, decreased hunting opportunities and availability of prey can lead to nutritional stress and reduced body size, and may affect reproductive success and survival (Molnár et al, 2011;Regehr et al, 2007;Rode et al, 2010Rode et al, , 2014. In some species, energetic stress may lead to suppression of the immune system and thereby increased mortality and reduced reproductive rates (e.g., Boonstra et al, 2001;Wayland et al, 2002).…”
Section: Introductionmentioning
confidence: 99%